Factors associated with awareness of breast cancer among women of reproductive age in Lesotho: a national population-based cross-sectional survey - Agani Afaya; Milipaak Japiong; Kennedy Diema Konlan; Solomon Mohammed Salia (BMC, 2023)
Abstract Background Breast cancer is a leading cause of cancer mortality and a major public health problem. The growing number of breast cancer-related deaths has been largely attributed to a lack of awareness of the disease among women. Whilst there have been frequent campaigns promoting breast cancer awareness, evidence suggests that women still lack awareness. Therefore, this study assessed the prevalence and factors associated with the awareness of breast cancer among women of reproductive age in Lesotho. Methods We used population-based cross-sectional data from the 2014 Lesotho Demographic and Health survey. A total of 6,620 women of reproductive age were included in the analysis. The outcome variable was awareness of breast cancer. Women who heard about breast cancer were considered to be aware of the disease. Multilevel binary logistic regression models were fitted to determine the factors associated with breast cancer awareness among women. Results The level of awareness of breast cancer was 86.8% (95% CI: 85.5, 87.9). Women aged 45-49 years [adjusted odds ratio (AOR) = 2.87, 95% confidence interval (CI): 1.83, 4.48], married women [AOR = 1.51 (95% CI: 1.19, 1.93)], and women with higher educational level [AOR = 12.56, (95% CI: 4.35, 36.28)] were more likely to be aware of breast cancer. Additionally, women who listened to the radio at least once a week [AOR = 1.96, (95% CI: 1.63, 2.37)], those who read newspapers or magazines [AOR = 1.91 (95% CI: 1.48, 2.46)] and women in the wealthiest group [AOR = 2.55, (95% CI: 1.67, 3.89)] had higher odds of breast cancer awareness. However, women who were in rural areas were less likely [AOR = 0.63, (95% CI: 0.47, 0.84)] to be aware of breast cancer than those in urban areas. Conclusion The level of awareness of breast cancer among women of reproductive age in Lesotho was extremely low. We recommend that policymakers, clinicians, and public health practitioners should consider the factors identified in this study when designing and developing intervention programs to improve the awareness of breast cancer among women in Lesotho.